2005
DOI: 10.1007/s00467-005-1868-y
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal transient renal failure with renal medullary hyperechogenicity: clinical and laboratory features

Abstract: Sonographic findings of renal medullary hyperechogenicity have been observed in the neonate in association with severe perinatal renal injury, kidney malformations or nephrocalcinosis, and, rarely, in newborn infants with transient renal failure. The aim of the study was to describe the entity of neonatal transient renal failure with renal medullary hyperechogenicity (NTRFMH). We studied nine term neonates, born between August 1999 and February 2004 in our institution (0.1% of the live born infants), who devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Makhoul et al 5 described nine term neonates who, after birth, developed transient renal dysfunction, oligoanuria and bilateral medullary hyperechogenicity, with excellent prognosis. Additional findings included proteinuria (100%), uric acid crystalluria (78%) and hyperuricaemia (44%), with mean creatinine of 1.09 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Makhoul et al 5 described nine term neonates who, after birth, developed transient renal dysfunction, oligoanuria and bilateral medullary hyperechogenicity, with excellent prognosis. Additional findings included proteinuria (100%), uric acid crystalluria (78%) and hyperuricaemia (44%), with mean creatinine of 1.09 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Increased medullary echogenicity disappeared once the dehydration was corrected and renal function improved. 5 When feeding was reinitiated the baby deteriorated possibly due to malrotation and mass effect in the thorax. Bag and facemask ventilation is contraindicated in CDH however, in our case the initial improvement was because the stomach had not herniated into the thoracic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported nonasphyxiated neonates who had transient anuric/oliguric acute renal injury with hyperechoic renal medullary pyramids that returned to normal hypoechoic appearance within 4 to 6 days as well as full clinical recovery and normalization of all laboratory test results. (6) The acute renal injury and hyperechoic renal pyramids are believed to be caused by excess production of Tamm-Horsfall proteins, causing transient renal tubular obstruction.…”
Section: Clinical and Imaging Featuresmentioning
confidence: 99%